2019
DOI: 10.3389/fimmu.2019.00016
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Soluble Receptors in Breast Milk as Enhancers of Oral Tolerance Development

Abstract: The postpartum period is an important window during which environmental factors can shape the life-long health of the infant. This time period often coincides with substantial milk consumption either in the form of breast milk or from cow's milk sources, such as infant formulas. Although breast milk is the most beneficial source of nutrients for infants during the first 6 months after birth, its role in regulating food allergy development, through regulation of oral tolerance, is still controversial. Breast mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 125 publications
1
55
1
3
Order By: Relevance
“…However, we cannot formally conclude that D pteronyssinus proteases are solely responsible for the cascade of immune events that are occurring in offspring nursed by D pteronyssinus-exposed mothers and other immune modulatory molecules in breast milk of D pteronyssinus-exposed mothers may play an additional role. 55,56 The observation that milk of mothers exposed to D pteronyssinus displayed an increased proteolytic activity using Der p 1 preferential substrate as compared to milk of PBS-exposed mothers or to milk of mothers exposed to D pteronyssinus allergen with no protease activity (protease-inactivated D pteronyssinus) suggests that maternal exposure to D pteronyssinus protease results in its transfer to the milk. We further confirmed that the increased proteolytic activity found in D pteronyssinuscontaining breast milk was not related to the potential release of mast-cell tryptase by neonates exposed to D pteronyssinus as similar levels of tryptase were found in milk collected from the stomach of pups nursed by mothers exposed to PBS or D pteronyssinus (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot formally conclude that D pteronyssinus proteases are solely responsible for the cascade of immune events that are occurring in offspring nursed by D pteronyssinus-exposed mothers and other immune modulatory molecules in breast milk of D pteronyssinus-exposed mothers may play an additional role. 55,56 The observation that milk of mothers exposed to D pteronyssinus displayed an increased proteolytic activity using Der p 1 preferential substrate as compared to milk of PBS-exposed mothers or to milk of mothers exposed to D pteronyssinus allergen with no protease activity (protease-inactivated D pteronyssinus) suggests that maternal exposure to D pteronyssinus protease results in its transfer to the milk. We further confirmed that the increased proteolytic activity found in D pteronyssinuscontaining breast milk was not related to the potential release of mast-cell tryptase by neonates exposed to D pteronyssinus as similar levels of tryptase were found in milk collected from the stomach of pups nursed by mothers exposed to PBS or D pteronyssinus (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β inhibits naïve T cells from differentiation into Th1 and Th2 subtypes, which promote cell mediated immune responses by secreting pro-inflammatory cytokines and promote IgE and eosinophilic responses, respectively. TGF-β also helps stabilize forkhead box P3 (FOXP3) expression and maintains the differentiation of T-regulatory cells which inhibit immune responses and temper inflammation [63]. In preterm infants, lower TGF-β levels preceded NEC development, underlining the significance of TGF-β in immune and inflammation regulation [64].…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…However, the key anti-inflammatory and immunoregulatory cytokine interleukin-10 (IL-10), is found in very high concentrations during the first 80 hours of lactation (Garofalo et al 1995). It has been suggested that IL-10 inhibits Th1 responses, contributes to the survival and expansion of B cells, and downregulates major histocompatibility complex-II (MHC-II) expression on monocytes (Dawod and Marshall 2019). Another regulatory cytokine found in breast milk is IL-7.…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%